A novel tool for measuring ankle dorsiflexion: A study of its reliability in patients following ankle fractures. Issue 4 (December 2016) - Larsen, Peter; Nielsen, Henrik B.; Lund, Christoffer; Sørensen, Daniel S.; Larsen, Birgit T.; Matthews, Mark; Vicenzino, Bill; Elsoe, Rasmus
Highlights: Weight bearing measurement of ankle dorsiflexion is critical in quantifying physical impairment in patients following ankle fractures. A lunge ankle dorsiflexion measurement device (LAD), has been devised. Assessment of ankle dorsal flexion using the novel LAD shows a high inter- and intra-tester reliability in patients following a fracture of the ankle joint. Abstract: Background: Assessment of ankle joint movement in a weight bearing position has important clinical implications. The lunge ankle dorsiflexion measurement device (LAD) has been developed with the aim of facilitating ease of and standardisation of the measurement of ankle joint movement. The literature lacks studies evaluating the reliability of weight bearing measurements of the ankle joint in study groups with ankle disabilities. The objective of this study was to examine the intra- and inter-tester reliability of ankle dorsiflexion measured with the novel LAD in patients following a fracture of the ankle. Method: This study was a randomized intra- and inter-tester reliability study with blinding of testers and participants. All participants were tested twice by each tester, with the order of testers randomized. The intra- and inter-tester reliability was assessed by the calculation of interclass correlation coefficients (ICC). Results: The study sample consisted of 24 patients: 15 females and nine males post-immobilisation following surgery for ankle fractures. The mean age was 51.0 years, ranging from 22 to 92 years. All patients had sustained an AO classification 44- fracture of the ankle. The mean follow-up time was 9.3 months (16.2 SD) after the time of fracture. The inter-tester reliability was high, with an ICC of 0.984 (95%CI: 0.963–0.993) and SEmeas of 0.14 cm. The ICC for Tester A was 0.989 (95%CI: 0.974–0.995) and SEmeas 0.10 cm. The ICC for Tester B was 0.990 (95%CI: 0.977–0.996) and SEmeas 0.09 cm. Conclusion: This study shows a high inter- and intra-tester reliability for measuring ankle dorsiflexion with the LAD following a fracture of the ankle.